Metamorfosis Lengkap Tidak Lengkap Dan Tanpa Metamorfosis - Suliastika Candra Wati; Silviana Romadani Putri; Cantika Puteri Hermadania Nurraya (Jurnal Pengabdian Pendidikan, 2025)
IPAS learning in elementary schools requires teaching materials that can present concepts concretely and attractively in accordance with students’ developmental characteristics. One topic that requires strong visual support is metamorphosis, as it involves abstract and chronological stages of change in living organisms. This study aims to examine the development of interactive comic-based IPAS worksheets (LKPD) on complete metamorphosis, incomplete metamorphosis, and non-metamorphosis materials through a literature study approach. The research employed a descriptive qualitative method using library research. Data were collected from various sources, including scientific journals, reference books, and relevant documents related to comics as learning media, LKPD, IPAS learning, and metamorphosis topics. Data analysis was conducted using content analysis techniques to identify concepts, research findings, and principles for developing interactive comic-based LKPD. The results indicate that interactive comics have significant potential to enhance learning motivation, facilitate conceptual understanding, and present metamorphosis material in a structured and concrete manner. Therefore, the development of interactive comic-based IPAS worksheets can serve as an innovative and relevant alternative teaching material to support IPAS learning in third-grade elementary schools.